Comparative study of physical growth and nutritional status of schoolchildren (1997 and 2009). - Zenite Machado; Ruy Jornada Krebs; Joiana Dias Prestes; Márcio Borgonovo dos Santos; João Otacílio\Libardoni dos Santos; Glauber Carvalho Nobre; Maria Helena Ramalho (Universidade Federal de Santa Catarina, 2011)
Physical growth and nutritional status are excellent health indicators since they permit the establishment of growth monitoring charts, especially for schoolchildren. The objective of this study was to compare the growth profile and nutritional status of schoolchildren between two samples (1997 and 2009). The data of physical growth and nutritional status obtained for the present sample of 645 schoolchildren (270 boys and 375 girls). The children were classified according to the body mass index (BMI)-for-age reference values of the WHO child growth standards. Although no significant differences in height or body weight were observed between the children studied, these variables tended to increase from the first to the second sample and in the two genders. With respect to the adequacy of BMI in boys, there was an increase in the percentage of children with low BMI-for-age, doubling of the percentage of obese children, and a reduction in the percentage of children with overweight. An increase in the number of subjects with low body weight, overweight and obesity and a decrease in the number of subjects with adequate BMI-for-age were noted among girls. In conclusion, there were no significant changes in the physical growth indicators (weight, height and BMI) over the period comprising the two samples (1997 and 2009). However, height, body weight and the number of subjects with risk of obesity and obesity tended to increase, especially among girls.